2018
DOI: 10.1111/jpn.12889
|View full text |Cite
|
Sign up to set email alerts
|

Digestive proteases and in vitro protein digestibility of feed ingredients for the Central American river turtle, Dermatemys mawii

Abstract: Functional characteristics of digestive proteases and in vitro digestibility of several protein sources were studied in hatchlings of Central American river turtles, Dermatemys mawii. Acidic and alkaline proteases from the stomach and intestines were used, and optimums for acidic proteases were registered at 55°C and pH 2, while alkaline proteases were found at 55°C and pH 9. Ten protein ingredients, both vegetable and animal sources, were explored by the pH-STAT method, only for alkaline proteases. The degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In Fig. 5, the results of SDS-PAGE revealed six bands with stomach after feeding in other reptile species such as white turtle (Dermatemys mawii) and the red-eared turtle (Trachemys scripta elegans) that show optimum acid protease activity at pH 2 and pH 2.5, respectively (Rangel-Mendoza et al, 2018;Sun et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 5, the results of SDS-PAGE revealed six bands with stomach after feeding in other reptile species such as white turtle (Dermatemys mawii) and the red-eared turtle (Trachemys scripta elegans) that show optimum acid protease activity at pH 2 and pH 2.5, respectively (Rangel-Mendoza et al, 2018;Sun et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This assumption is corroborated by the optimum activity obtained for trypsin and leucine aminopeptidase, which shows the highest activity at pH 10 and pH 8, respectively. Studies in reptiles such as the white turtle (Dermatemys mawii), show optimum alkaline protease activity at pH 9 (Rangel-Mendoza et al, 2018), while the redeared turtle (Trachemys scripta elegans) shows optimum pH in pancreas, and foregut, midgut, and hindgut of 8.0, 7.0, 8.0, and 8.5, respectively (Sun et al, 2007). Tracy et al, (2015), reported the digestive morphology, the activity of membrane enzymes (aminopeptidases, maltase and sucrase) and the absorption of nutrients in Alligator mississippiensis and Crocodylus porosus, where it was found that the villi of the proximal intestine varied in the two species, having A. misisipiensis the highest absorption and aminopeptidase activity compared to C. porosus.…”
Section: Discussionmentioning
confidence: 99%